A novel allele, HLA‐B*54:29, identified by sequence‐based typing in a Chinese bone marrow donor. Issue 6 (27th March 2014) - He, J.‐J.; Wang, W.; He, J.; Zhu, F.‐M.; Lv, H.‐J.
<x xml:space="preserve">Abstract</x> HLA‐B*54:29 allele differs from B*54:01:01 at nucleotide position 442 A>C in exon 3.